MTsN 2 Aceh Selatan محاولة المدرّس لحل المشكلات في تدريس اللغة العربية بــــ - Radhiani, Sri Mulya; Hasyim, Syarifuddin; Marzuki, Marzuki (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2021)
The purpose of this research is to find out the efforts of Arabic language teachers to overcome the difficulties of learning Arabic. The research method used is descriptive analysis. The data collection techniques used is interview Arabic language teacher. The data analysis techniques in this study use the theory of Miles and Hubberman including : Data Collection, Data Reduction, Data Display, and conclution. The efforts of Arabic language teachers to overcome the difficulties Arabic learning at MTsN 2 Aceh Selatan are The teacher give motivation to students to increase enthusias and interes students, Multiplying textbooks in the library so that students can borrow to facilitate the learning process, giving vocabularies to memorize making it easier for students to understand the material, Using media, and also use other methods in the process of learning Arabic.